Niche-specific adaptation of Lactobacillus helveticus strains isolated from malt whisky and dairy fermentations - Kido, Yoshihiko (Microb Genom, 2021)
Lactobacillus helveticus is a well characterized lactobacillus for dairy fermentations that is also found in malt whisky fermentations. The two environments contain considerable differences related to microbial growth, including the presence of different growth inhibitors and nutrients. The present study characterized L. helveticus strains originating from dairy fermentations (called milk strains hereafter) and malt whisky fermentations (called whisky strains hereafter) by in vitro phenotypic tests and comparative genomics. The whisky strains can tolerate ethanol more than the milk strains, whereas the milk strains can tolerate lysozyme and lactoferrin more than the whisky strains. Several plant-origin carbohydrates, including cellobiose, maltose, sucrose, fructooligosaccharide and salicin, were generally metabolized only by the whisky strains, whereas milk-derived carbohydrates, i.e. lactose and galactose, were metabolized only by the milk strains. Milk fermentation properties also distinguished the two groups. The general genomic characteristics, including genomic size, number of coding sequences and average nucleotide identity values, differentiated the two groups. The observed differences in carbohydrate metabolic properties between the two groups correlated with the presence of intact specific enzymes in glycoside hydrolase (GH) families GH1, GH4, GH13, GH32 and GH65. Several GHs in the milk strains were inactive due to the presence of stop codon(s) in genes encoding the GHs, and the inactivation patterns of the genes encoding specific enzymes assigned to GH1 in the milk strains suggested a possible diversification manner of L. helveticus strains. The present study has demonstrated how L. helveticus strains have adapted to their habitats.